Oral health knowledge regarding dental caries among a group of middle school students - Ruxandra Sfeatcu; Roxana Oancea; Cristian Dăguci; Irina Maria Gheorghiu; Sânziana Adina Scărlătescu; Paula Perlea (Amaltea Medical Publishing House, 2019)
Introduction. Schools are favorable environment for information dissemination on disease prevention and sup-porting the health-related behaviors in oral education and promotion programs. Material and methods. The study comprised 240 middle school students aged between 10 and 15 years, 57.5% of whom were female. Pupils received an anonymous questionnaire on the level of knowledge about risk factors for tooth decay and caries prevention methods and then an oral health experiential education lesson. Results. The knowledge level is relatively high in terms of sugar consumption and tooth brushing role on dental caries. Subjects are less informed about the involvement of the dental plaque and other risk factors. Family is the main source of oral health information, and many students rarely visit the dentist. Conclusion. There is a need for preventive programs in schools, involving teachers and parents to develop a favorable environment to health education.